2020
DOI: 10.1101/2020.10.04.324525
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

CXCL10+peripheral activation niches couple preferred sites of Th1 entry with optimal APC encounter

Abstract: SUMMARYCorrect positioning of T cells within infected tissues is critical for T cell activation and pathogen control. Upon tissue entry, effector T cells must efficiently locate antigen presenting cells (APC) for peripheral activation. We reveal that tissue entry and initial peripheral activation of Th1 effector T cells are tightly linked to perivascular positioning of chemokine-expressing APCs. Dermal inflammation induced tissue-wide de novo generation of discrete perivascular CXCL10+ cell clusters, enriched … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(14 citation statements)
references
References 52 publications
0
14
0
Order By: Relevance
“…A third study showed that vaccination of mice induced an IFNg/CXCR3-dependent spatial hub of T cells and myeloid cells expressing CXCL10. This hub formed around the vasculature and facilitated entry of circulating T cells into the tissue (Prizant et al, 2021), providing a platform for frequent encounters of T cells with other cells to coordinate immune responses.…”
Section: Discussionmentioning
confidence: 99%
“…A third study showed that vaccination of mice induced an IFNg/CXCR3-dependent spatial hub of T cells and myeloid cells expressing CXCL10. This hub formed around the vasculature and facilitated entry of circulating T cells into the tissue (Prizant et al, 2021), providing a platform for frequent encounters of T cells with other cells to coordinate immune responses.…”
Section: Discussionmentioning
confidence: 99%
“…A third study showed that vaccination of mice induced an IFNG/CXCR3-dependent spatial hub of T cells and myeloid cells expressing CXCL10. This hub formed around the vasculature and facilitated entry of circulating T cells into the tissue 66 , thus providing a platform for frequent encounters of T cells with other cells to coordinate immune responses.…”
Section: Discussionmentioning
confidence: 99%
“…While the recent study of the adventitial cuff suggests this pre‐positioned innate activation niche can also serve as a site for subsequent effector T cell activation, 103 it remains unclear whether the induced clustering of effector T cells with APCs seen in many inflamed tissues (Table 1) arises at predetermined locations within the tissue parenchyma. A growing body of evidence points to the de novo assembly of microanatomical activation hubs located perivascularly that are induced following immune challenge and that underpin T cell immunity within inflamed tissues 4,5,7,8,86,117‐119 …”
Section: T Cell Activation Niches In Peripheral Tissuesmentioning
confidence: 99%
“…The specific immune cells recruited to this niche will likely differ depending on the tissue and the type of pathogen; however, common themes are emerging. The induction of innate signals, such as type 1 interferons, initiate the activation and recruitment of myeloid subsets to the perivascular space, where local niche‐specific chemokine production and antigen presentation optimizes encounter with incoming effector T cells 4,5 . It is not yet known if the induced perivascular niche arises from any strategic positioning that might optimize enrichment of antigen, as seen in the SCS of the LN or the adventitial cuff.…”
Section: T Cell Activation Niches In Peripheral Tissuesmentioning
confidence: 99%
See 1 more Smart Citation